The Effects of the Earned Income Tax Credit on Children's Health, Quality of Home Environment, and Non-Cognitive Skills - Susan L. Averett; Yang Wang (Institute for the Study of Labor (IZA), 2015)
In 1993, the benefit levels of the Earned Income Tax Credit (EITC) were changed significantly based on the number of children in the household. Employing a difference-in-differences plus mother fixed-effects framework, we find better mother-rated health for children of unmarried black mothers and married white and Hispanic mothers, lower accident rates for children of married white and Hispanic mothers, and improved home environment quality for children of unmarried white and Hispanic mothers. Our results provide new evidence of the effects of the 1993 EITC expansion and therefore have important policy implications.
Keywords: I12; I38; J13; 330; EITC; child health; home environment; non-cognitive skills